Analisis Trend, Peramalan, dan Penentuan Daerah Basis Komoditas Padi di Provinsi Sumatera Barat - Hendra Alfi; Fajri; Andreas Sitanggang; Benny Warman R; Aflizar; Irwan A; Angga Defrian (Fakultas Pertanian Universitas Ratu Samban, 2024)
Paddy has become a strategic commodity in Indonesia's national food security system with its dominant role as a staple food source for most people. As one of the main paddy producing areas in Indonesia, West Sumatra Province has quite significant production dynamics in the last few years. This study aims to analyze the trend of paddy production in West Sumatra Province, predict the amount of paddy production in West Sumatra Province, and identify the paddy commodity base areas in West Sumatra Province. The results of the study showed that paddy production in West Sumatra. The methods used in this study were descriptive analysis, Least Square, and Location Quotient (LQ). The results showed that throughout 2018-2024 paddy production in West Sumatra showed a negative trend with an average decline of 22,429.18 tons per year and it is predicted that in 2025-2029 it will experience a decline with an average of 26,307.81 tons per year. Of the 19 regencies/cities in West Sumatra Province, there are 14 areas that are paddy commodity base areas in West Sumatra.